The relation of peak body acceleration to phases of movements in swimming - Ungerechts, B. E. (Swimming Science V, 1988)
The question of the manner in which propulsion in aquatic surroundings is produced by repeated cyclic actions of body parts concerns physiologicat hydrodynamic, and functional/morphological aspects. Only if one succeeds in taking all these factors into account may a more satisfying answer be found than is currently available. The objective of this article is to discuss the functional/morphological and hydrodynamic causes (some temporal aspects) of the acceleration related to swimming movements during the breaststroke. The intracyclic acceleration of a swimming body is the sum of the resultant braking and propelling forces and is basically the origin of swimming speed. The movement of a swimming body can be described as periodically changing. In competitive swimming these intracyclic fluctuations are considered to limit swimming performance and depend on the swimmer's skill (Toussaint et al., 1983). This might imply that basically the fluctuations can be omitted as is possible when driving a car. A car's shape is designed to produce less resistance. The mechanics of the engine are not affected by the air flow, whether it is laminar or turbulent. Engine work and air flow, then, have nothing in common. Because the swimmer acts as a sell-propelling body, the propelling part and braking area are not separated as in a car. In self-propelling bodies, propulsive forces depend on the change of the body form, its frequency, and its amplitude, so changing shape must be taken into account. The resistive forces can be attributed to the same parameters. The combinations of movement, shape, and type of flow are determinants of the amount of propulsion. Muscular activity alone will not produce any propulsion. The same "undulating" body simultaneously produces resistive and propulsive forces, a situation that cannot be compared to a rigid car with a steady flow. In contrast, self-propelling bodies create a nonsteady flow. Hydrodynamic studies reveal that the flow along an "undulating" body is a fluctuating flow (Ungerechts, 1983), and the research indicates that this fluctuating flow influences the boundary layer along the body. In breaststroke Barthels (1979) compared the propulsive mechanism of the breaststroke kick with the mechanism of the sculling hands, the so called lift force handle. Barthels points out that "the feet are sculling and remain in a vertical section of water while the body moves forward in response to leg extension" (p. 53), creating a force wall If a force wall can be produced, then the peak acceleration depends on the functional properties of the knee extensors, that is, their temporal development of forces or moments, respectively. On the other hand, the question remains, Do the upper and lower extremities create the "force wall" according to the same hydrodynamic principles?